2022
DOI: 10.1177/00369330221088928
|View full text |Cite
|
Sign up to set email alerts
|

Tangible effects of the COVID-19 pandemic: A fall in dexterity amongst surgical trainees?

Abstract: Background The coronavirus pandemic has had an indisputable impact on surgical training. The qualitative effect on the perceived confidence and capability of trainees has been widely reported. In order to fully delineate the scope of the problem, quantitative data is also required. Methods This cross-sectional study collected compared data on the laparoscopic skills (pre- and post-pandemic) of first-year urology residents in the United Kingdom, who attended the annual Urology Simulation Boot Camp (USBC) in 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…The impact of organized formal teaching being changed to a virtual platform was investigated by one study [24]. Surgery was the specialty that had the greatest number of studies ( 14) on the topic [4,5,[8][9][10][11][14][15][16][17][18][19]21,23]. Four were not associated with any particular specialty [2,3,22,24].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The impact of organized formal teaching being changed to a virtual platform was investigated by one study [24]. Surgery was the specialty that had the greatest number of studies ( 14) on the topic [4,5,[8][9][10][11][14][15][16][17][18][19]21,23]. Four were not associated with any particular specialty [2,3,22,24].…”
Section: Reviewmentioning
confidence: 99%
“…One study focused on those at the beginning of their training, looking at the impact of the introduction of an "interim" doctor role for medical students who were months away from completing medical school [ 22 ]. One study assessed if there had been any change in the technical skills of trainee surgeons, analyzing the results of simulated tasks from before and after the pandemic [ 23 ]. The impact of organized formal teaching being changed to a virtual platform was investigated by one study [ 24 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“… 1 , 2 The temporary cessation of skill courses and conferences by the organisations and professional bodies have impacted training of future surgical workforce. In this issue Ms Gowda et al 3 report, impact of Covid-19 pandemic on the technical skills of urology trainees attending national BOOTS camp. 4 The study finds a detrimental effect of pandemic on the technical skills of trainees, whereas a similar study by Etheridge et al from Singapore 5 showed an improvement in non-technical and team management skills.…”
mentioning
confidence: 99%